Community services Community services in an effort to utilize household food waste as organic fertilizer in addition to bioactivators in Balikpapan - Merry Krisdawati Sipahutar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2021)
Lack of household food waste management results in major environmental problems, such as bad smells and dirt, as well as greenhouse gas emissions, which adversely affect public health. The goal of this community services was to transform household food waste into organic fertilizer, so agricultural output, economize resources, and public health can be increased. The method used in this service was that of individual or one-on-one and group counseling. The benefit of the activity was to produce high-value compost generated from househol food waste and utilization of local resources. After conducting the community services, found that that the community of Klandasan Ulu in Balikapan, who was involved in the training on household food waste management, fathomed how to discover household food waste to become organic fertilizers with economic and environmental value by adding bioactivators at room temperature and facultative aerobic condition. The impact of this training on patterns of community garbage disposal action was also observed.